Stroke onset time estimation from multispectral quantitative magnetic resonance imaging in a rat model of focal permanent cerebral ischemia. Issue 6 (August 2016) - McGarry, Bryony L; Rogers, Harriet J; Knight, Michael J; Jokivarsi, Kimmo T; Sierra, Alejandra; Gröhn, Olli HJ; Kauppinen, Risto A
Background: Quantitative T2 relaxation magnetic resonance imaging allows estimation of stroke onset time. Aims: We aimed to examine the accuracy of quantitative T1 and quantitative T2 relaxation times alone and in combination to provide estimates of stroke onset time in a rat model of permanent focal cerebral ischemia and map the spatial distribution of elevated quantitative T1 and quantitative T2 to assess tissue status. Methods: Permanent middle cerebral artery occlusion was induced in Wistar rats. Animals were scanned at 9.4T for quantitative T1, quantitative T2, and Trace of Diffusion Tensor (Dav ) up to 4 h post-middle cerebral artery occlusion. Time courses of differentials of quantitative T1 and quantitative T2 in ischemic and non-ischemic contralateral brain tissue (ΔT1, ΔT2 ) and volumes of tissue with elevated T1 and T2 relaxation times ( f 1, f 2 ) were determined. TTC staining was used to highlight permanent ischemic damage. Results: ΔT1, ΔT2, f 1, f 2, and the volume of tissue with both elevated quantitative T1 and quantitative T2 (V Overlap ) increased with time post-middle cerebral artery occlusion allowing stroke onset time to be estimated. V Overlap provided the most accurate estimate with an uncertainty of ±25 min. At all times-points regions with elevated relaxation times were smaller than areas with Dav defined ischemia. Conclusions: Stroke onset time can be determined by quantitative T1 and quantitative T2 relaxation times and tissue volumes. Combining quantitative T1 and quantitative T2 provides the most accurate estimate and potentially identifies irreversibly damaged brain tissue.